Evaluation of Materials for Grade 10 Secondary School Students - Wulandari Santoso (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2022)
The use of course book has become a debatable issue, especially in the field of English Language Teaching. Its use is deemed useful as it could provide a clear organization of the lesson, a syllabus, and a guideline for teachers to select materials for students. Nevertheless, it could also be argued that the use of course book also present some issues, for example, some teachers may rely on course book without making informed decisions about how to use it appropriately. This study aimed to evaluate a course book used in a secondary high school. The evaluation focused on how the course book accommodate students’ speaking skills and learning styles. The course book was analyzed using both external and internal checklists adapted from current literature. In addition, the analysis of institution, teacher, and student needs were also conducted in order to see whether the course book fulfilled their needs. The results showed that the external evaluation did not demonstrate any issues. However, the internal evaluation revealed that the tasks did not cater most students’ learning styles as well as communicative activities. This study recommends further material adaptation and supplementation for this course book to better suit the teaching context.